The Native Scientist project in Ireland: Promoting Heritage Languages through informal Engagements with Scientists - La Morgia, Francesca; Correia, Tatiana; Moscoso, Joana A. (My University, 2018)
This project report focuses on the results of a series of heritage language STEM workshops which were run in Ireland by the organization Native Scientist. The results indicate that the workshops represent a positive experience for children and scientists, and show high potential to enhance the linguistic skills of bilingual pupils.
PUBLISHED
Keywords: Native Scientist; Heritage language; STEM; Identities in Transformation; Inclusive Society; Making Ireland; CHILD LANGUAGE; Language and Immigration in Ireland